THE ROLE OF WORK ENTHUSIASM IN MEDIATING THE INFLUENCE OF COMPETENCE ON THE PERFORMANCE OF BANK SUMSEL BABEL SYARIAH EMPLOYEES - Seftriani Arimbi Putri ER; Aryanto, Rudi; Said Abdullah Syahab (I-Finance Journal, 2024)
This study aims to analyze the role of work enthusiasm in mediating the effect of competence on employee performance of Bank Sumsel Babel Syariah KC Palembang. This research method involves the use of a Likert scale as an assessment instrument. The population in this study were all employees of Bank Sumsel Babel Syariah Palembang Branch Office, totaling 35 people. The sample was taken using saturated sampling, namely all employees of Bank Sumsel Babel Syariah Palembang Branch Office were taken as a sample of 35 people. The analysis technique uses path analysis with the SEM PLS application. This study produces findings that competence affects employee performance, and the work enthusiasm variable also has an influence on employee performance, as well as competence affects work enthusiasm. However, work enthusiasm is not able to mediate the effect of competence on employee performance of Bank Sumsel Babel Syariah Office Palembang Branch Office. The conclusion shows that competence and work enthusiasm affect employee performance, competence affects work enthusiasm and work enthusiasm is not able to mediate the effect of competence on employee performance of Bank Sumsel Babel Syariah Office Palembang Branch Office